Emotional Intelligence among teachers and future teachers in a sample of Spanish educators - Romeu, Marta Valle (2021)
Emotional Intelligence (EI), defined by Salovey and Mayer (1990, p. 189) as “the ability to monitor one's own and other people's emotions, to discriminate between different emotions and label them appropriately, and to use emotional information to guide thinking and behaviour”, would appear to be necessary for those who work with and educate children, adolescents, and, ultimately, individuals who are still developing their cognitive abilities and personal traits. This quantitative study investigated emotional intelligence using the answers to a self-report Emotional Intelligence questionnaire developed by Petrides (2009). The questionnaire yielded scores on four different constructs of Emotional Intelligence as well as an overall score. A sample of 77 Spanish educators, 42 of whom were future teachers and 35 experienced teachers, participated in the research. The analysis indicated that the levels of Emotional Intelligence (EI) of the sample of educators were relatively high. It also showed a little, but statistically significant difference between the levels of Emotional Intelligence of teachers and future teachers, being the means always higher for teachers. The analysis showed no statistically significant difference in gender or teachers’ experience. It was also observed that participants’ high scores in some factors of the test were correlated to high results in other factors. Overall, the results reveal that the levels of EI of the sample who participated in the study are relatively high, but the differences between experienced and future teachers were small. Future research could aim at develop programs targeted at developing the emotional intelligence of teachers in Spain.